Contractual Transaction: How Renting a Uterus Makes the Human Body a Commodity in Nepal - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2015)
The issue of surrogate motherhood has started public debates in Nepal. With surrogacy a child becomes the object of a legal transaction, while the surrogate mother is used, in effect as an incubator, and the hospital declares commissioned parents’ name of a newborn child. The poor women in low-income countries have been used as means to compensate for the reproductive deficiencies of high-income infertile parents. Do purchasing cheaper services, receiving surrogates easier, and having the possibility of gender selection, all in the poor countries, support ‘surrogacy tourism’ or is it a kind of exploitative relationship? Until today, Nepal’s laws do not have any specific provision to deal with surrogacy and, therefore, it is urgent to address the challenges with commercial surrogacy and establish a precise legal policy.